Framing Of Media Discourse On Television: A Comparative Study Of Aljazeera And Al -hadath Channels On The Boycott Of Products From Companies Supporting The Zionist Entity - Akrem Boutora; Radouane Belkhir (The Journal of Studies in Language, Culture and Society, 2025)
The paper entitled Framing Communication Discourse Over Television: A Comparative Examination of Al Jazeera and Al Hadath Channels on the Boycott of Goods from Establishments Helping the Zionist Entity investigates how the broadcasting determines public opinion through linguistic and textual scrutiny based on frame theory and agenda setting. The researchers used quantitative and qualitative methods to examine text and linguistic information and to provide a detailed comparison of the major vocabulary and phrases used simultaneously in different channels. The delve into exposes that al Jazeera adopts an aggressive, boycotting discourse, stresses ideas of resistance and privileges while attaching the subject to a transnational, political, and monetary dimension. Rather, al Hadath focused on the local consequences of the boycott, including the implications for consumers and the state economy. In addition, the inquiry claims that the difference in discourse strategies reflects changes in ideological and public orientation, which in turn affects the way the audience's knowledge is designed and how it is counterbalanced in relation to the question at issue. In its resolution, the Post stresses the importance of assessing broadcasting discourse in order to understand the current social and government activity in the region.